2016
DOI: 10.1002/anie.201511646
|View full text |Cite
|
Sign up to set email alerts
|

Highly Unsaturated Platinum and Palladium Carbenes PtC3 and PdC3 Isolated and Characterized in the Gas Phase

Abstract: Carbenes of platinum and palladium, PtC3 and PdC3, were generated in the gas phase through laser vaporization of a metal target in the presence of a low concentration of a hydrocarbon precursor undergoing supersonic expansion. Rotational spectroscopy and ab initio calculations confirm that both molecules are linear. The geometry of PtC3 was accurately determined by fitting to the experimental moments of inertia of twenty‐six isotopologues. The results are consistent with the proposal of an autogenic isolobal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…With the extension to the millimetre range, (29) laboratory broadband measurements can also be combined with radio-telescope observations for the assignment of chemical species in the interstellar medium. (30) Additionally, metal complexes, (31,32) plasmas, (33) flash pyrolysis reaction intermediates, (34) and Rydberg transitions (35) have also been investigated using CP-FTMW spectroscopy.…”
Section: Catching Handedness In the Gas Phase -A New Avenuementioning
confidence: 99%
“…With the extension to the millimetre range, (29) laboratory broadband measurements can also be combined with radio-telescope observations for the assignment of chemical species in the interstellar medium. (30) Additionally, metal complexes, (31,32) plasmas, (33) flash pyrolysis reaction intermediates, (34) and Rydberg transitions (35) have also been investigated using CP-FTMW spectroscopy.…”
Section: Catching Handedness In the Gas Phase -A New Avenuementioning
confidence: 99%
“…Since Ir – , Pt, and Au + have the same number of electrons, we assume that Ir – may have similar chemical properties to those of the Pt and Au + . Previous studies have indicated that PtC 3 and AuC 3 + are linear structures with an MCCC characteristic. , To verify our assumption, photoelectron spectra and quantum calculations are performed to study the MC 3 – (M = Ir and Pt) clusters. We find that IrC 3 – and PtC 3 have structures that are similar to those of AuC 3 + and OC 3 .…”
mentioning
confidence: 66%
“…The Pt 3 C + cluster ion has been observed by infrared multiple photon dissociation (IRMPD) spectroscopy, whose geometry was similar to that of the carbonate ion, consistent with the empirical model predictions. In addition, the similarity between PtC 3 and OC 3 has been also proved by rotational spectroscopy . Previous theoretical calculations have revealed analogies between the behavior of each of Au + and Pt and O atom .…”
mentioning
confidence: 68%
See 2 more Smart Citations